Insecticide resistance dynamics in Anopheles gambiae s.l. in Ghana - Owusu-Asenso, Christopher Mfum; Abdulai, Anisa; Sraku, Isaac Kwame; Acquah, Yasmeen Amandi; Yanney, Stephina Adjoa; Dortey, Miriam DedeAma; Akuamoah-Boateng, Yaw; Sabtiu, Abdul Rahim Mohammed; Azumah, Judith Dzifa; Ebuako, Abena Ahema; Arhin, Grace Danquah; Amoateng, Godfred; et al. (Gigabyte, 2025)
Malaria control in Ghana, and indeed sub-Saharan Africa, is threatened by widespread insecticide resistance in Anopheles gambiae s.l., undermining the effectiveness of long-lasting insecticidal nets and indoor residual spraying. A longitudinal survey was conducted between 2023 and 2025 across 20 urban and suburban sites spanning the coastal savannah, forest, and Sahel savannah zones. Out of the total 1,008 An. gambiae s.l. sampled, An. coluzzii was the dominant species (65.1%), followed by An. gambiae s.s. (18.9%) and An. arabiensis (10.9%). WHO bioassays revealed high pyrethroid resistance [mortality rate (MR) = 20% - 45%]. Full susceptibility to pirimiphos-methyl (MR = 99–100%) and chlorfenapyr was observed in most sites, though resistance to clothianidin occurred in Obuasi, Tema, and Abossey Okai. Intensity assays confirmed strong pyrethroid resistance even at 10× diagnostic concentrations. Genotyping showed near-fixation of the kdr L995F allele and the presence of additional resistance markers including N1570Y, V402L, I1527T, and Ace-1R G280S.